A pathmaker: tributes to Vina Mazumdar - Kasturi, Leela.; Sharma, Kumud.; Sarkar, Lotika.; Mazumdar, Vina; Centre for Women's Development Studies (New Delhi, India) (Rainbow Publishers, 2002)
Collection of tributes to Vina Mazumdar on her contribution to women's studies in India.
"Centre for Women's Development Studies."
Collection of tributes to Vina Mazumdar on her contribution to women's studies in India.
Keywords: Women's studies / India.